(untitled) (Academia Journal of Medicine, 2020)
Background: India experiencing an alarming increasing the burden of non-communicable diseases, like the prevalence of obesity and diabetes mellitus. Prevalence of CKD is also rising parallel but about this disease studied done infrequently, so the data on incidence of CKD is sparse. Cardiovascular disease can causing 50% fatality in these patients irrespective of biological age. According to international registries death in dialysis population that are occurring due to cardiac disease occurring up to 40%. Cardiovascular related morbidity and mortality that are associated with LVH is highly analytical for future progression that occurring in CKD patients.Subjects and Methods: This study was done in the Department of Medicine of TMMC & RC, TMU, MORADABAD, U.P. it was a Cross-sectional Observational Study.100 cases will be taken from OPD and IPD setting in TMMC & RC, TMU, Moradabad, U.P.Diagnosed cases of CKD patients aged >18 years of both sexes admitted in IPD or visiting to OPD in Teerthanker Mahaveer medical College & Hospital, Moradabad. Those who were give valid consent.Cases below 18years of age, pregnant women. All cases of acute renal failure. All known primary case of IHD, CHF, RHD, Cardiomyopathies and any other cardiac disorders.Results:Majority (54.0%) of sample were in the age group of 54 and above years, most (64.0%) of them were males.It revealed that, the mean body weight of the sample was 55.0±8.42 Kg, the mean Systolic Blood Pressure (mmHg) of the sample was 144.56±19.88 mmHg. Mean Diastolic Blood Pressure (mmHg) of the sample was 91.02±9.23 mmHg.ECG revealed that, around 65% of the sample had LVH.2-D ECHO-LVH/LV Function reveled that, around 36% AND 33% of the sample have Mild concentric LVH and Moderate LV systolic dysfunction and LVH respectively.Majority (71.0%) of the sample have reduced ejection fraction.Conclusion:Left ventricular hypertrophy and dysfunction is a veryimportant preventive feature of CKD associated cardiomyopathy.There is increased chance of left ventricular hypertrophy in CKD patients.With respect to category of chronic kidney disease, the LVH prevalence is progressively increases with increasing severity of CKD (chronic kidney disease).Blood pressure control is very important step to forestall the development of CKD and other related damage of end organs.